A COMPARATIVE ANALYSIS OF INDONESIAN AND MALAYSIAN REGULATORY APPROACHES TO PROMOTING ISLAMIC FINTECH FOR GLOBAL LEADERSHIP - Anjarwati, Ellyana (Proceeding of International Conference on Multidisciplinary Research, 2024)
The rapid growth of Islamic fintech in Southeast Asia positions Indonesia and Malaysia as key drivers in the advancement of Islamic finance. Although both countries share similar goals, they face distinct challenges. Their regulatory frameworks strive to foster technological innovation while ensuring Sharia compliance. This study provides a comparative analysis of the regulatory frameworks in Indonesia and Malaysia focusing on the integration of blockchain, artificial intelligence (AI), and Environmental, Social, and Governance (ESG) principles into Islamic fintech regulation. Through a systematic review, this research explores how each country addresses regulatory gaps and enhances financial inclusion. The findings highlight that Malaysia’s proactive approach, guided by the Islamic Financial Services Act (IFSA) 2013 and initiatives like MyDigital, has accelerated fintech development. In contrast, Indonesia’s regulatory efforts, outlined in the OJK Roadmap 2024–2028, aim to expand access to financial services but face hurdles related to infrastructure and Sharia financial literacy. The collaboration between both countries presents a unique opportunity to establish regional regulatory standards that can be adopted across ASEAN. Additionally, incorporating ESG principles into Islamic fintech is critical to attracting global investors, especially those focused on ethical finance. This study provides actionable insights for policymakers and industry leaders to develop adaptable and inclusive regulatory frameworks for sustainable growth.